Molecular markers of cartilage breakdown and synovitis at baseline as predictors of structural progression of hip osteoarthritis. The ECHODIAH Cohort. Issue 3 (1st December 2005) - Mazières, B; Garnero, P; Guéguen, A; Abbal, M; Berdah, L; Lequesne, M; Nguyen, M; Salles, J-P; Vignon, E; Dougados, M
Abstract : Objective: To determine whether systemic markers of bone, cartilage, and synovium can predict structural progression of osteoarthritis (OA). Methods: Patients with painful hip OA were treated with diacerein or placebo in a multicentre, prospective, double blind, 3 year follow up trial. The following information was collected at entry: demographics, characteristics of hip OA, and 10 markers: N-propeptides of collagen types I and III, cartilage oligomeric matrix protein, YKL-40, hyaluronan (sHA), matrix metalloproteinases-1 and -3, C reactive protein, C-terminal crosslinking telopeptides of collagen types I and II (uCTX-II). Radiographs were obtained at entry and every year. Structural progression was defined as a joint space decrease ⩾0.5 mm or requirement for total hip replacement. Grouped survival analysis was performed with time to structural progression as dependent variable, and clinical data, radiographic findings, treatment groups (diacerein versus placebo), and markers as explanatory measures. Results: In the 333 patients in whom all markers were measured, high functional impairment, a joint space width <2 mm, and lateral migration of the femoral head at baseline increased the risk of progression, but diacerein had a protective effect (relative risk = 0.75; 95% confidence interval (CI) 0.54 to 0.96). In addition, patients in whom uCTX-II and sHA were in the upper tertile had a relative risk of progression of 3.73 (95% CI 2.48 to 5.61) compared with patients with markers in the two lower tertiles. Conclusion: In this large cohort, combined measurements of uCTX-II and sHA were a new predictor of the structural progression of hip OA.